COMPARISON OF PHYSIOLOGICAL REACTIONS AND PHYSIOLOGICAL STRAIN IN HEALTHY MEN UNDER HEAT STRESS IN DRY AND STEAM HEAT SAUNAS - W. Pilch; Z. Szygula; T. Palka; P. Pilch; T. Cison; S. Wiecha; Ł. Tota (Termedia Publishing House, 2014)
The aim of the paper was to follow up major physiological reactions, provoked by heat stress during dry and wet sauna baths. A physical strain index and subjective estimation of heat comfort of subjects who had not taken sauna baths before was also evaluated. Ten healthy males aged 25-28 underwent a dry sauna bath and then after a one-month break they underwent a steam sauna bath. Each time, they entered the sauna chamber 3 times for 15 minutes with five-minute breaks. During breaks they cooled their bodies with a cold shower and then rested in a sitting position. Before and after the baths, body mass and blood pressure were measured. Rectal temperature and heart rate were monitored during the baths. The physiological strain index (PSI) and cumulative heat strain index (CHSI) were calculated. Subjects assessed heat comfort by Bedford's scale. Greater body mass losses were observed after the dry sauna bath compared to the wet sauna (-0.72 vs. -0.36 kg respectively). However, larger increases in rectal temperature and heart rate were observed during the wet sauna bath (38.8% and 21.2% respectively). Both types of sauna baths caused elevation of systolic blood pressure, but changes were greater after the dry one. Diastolic pressure was reduced similarly. Subjective feelings of heat comfort as well as PSI (4.83 ± 0.29 vs. 5.7 ± 0.28) and CHSI (76.3 ± 18.4 vs. 144.6 ± 21.7) were greater during the wet sauna bath. It can be concluded that due to high humidity and reduction of thermoregulation mechanisms, the wet sauna is more stressful for the organism than the dry sauna, where the temperature is higher with low humidity. Both observed indexes (PSI and CHSI) could be appropriate for objective assessment of heat strain during passive heating of the organism.